Planning tourism in protected natural areas: safety, soft law and conflict management between beach users. the case of surf in Aljezur, Portugal - Machado, Virgílio (2021)
The intensification of tourism in coastal areas can increase planning problems, with potential conflicts amongst beach users affecting their safety perceptions and, ultimately, their tourist experience. Therefore, this constitutes an important concern for local authorities. The present study was conducted on an environmentally sensitive tourism destination located in a protected natural area in the Algarve, Portugal, with a quite significant level of surf tourism activities-the Aljezur municipality. In total, 245 surfers and 282 bathers were surveyed as these beach user groups have been observed to have a potential for intergroup conflict. Data were collected regarding their perceptions of personal safety, conflicts between beach users, and conflict management strategies. The respondents were also surveyed regarding how local authorities can provide strategies of soft law for a more sustainable management of surfing tourism. The findings revealed a consensus about the safety of Aljezur beaches and existence of perceived low conflict levels amongst beach users. The strategies more valued by respondents to promote surfing tourism development in the territory include the preservation of the natural resources and the developed of local regulation. Overall, these findings can be useful to the sustainable management of the surfing tourism in the territory.